The Myth of the Chemical Cure - Moncrieff, J. author. aut Link
XI, 278 p.
Keywords: This book overturns the idea that psychiatric drugs work by correcting chemical imbalance and analyzes the professional, commercial and political vested interests that have shaped this view. It provides a comprehensive critique of research on drugs including antidepressants, antipsychotics and mood stabilizers.